Optimization of Digital Marketing Using Search Engine Optimization (SEO) at Soevenir CV Saudagar Kaya Abadi Malang - Nanul, Angela Marici; Islamiyah, Mufidatul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to explore the effectiveness of digital marketing using Search Engine Optimization (SEO) on social media platforms for CV Saudagar Kaya Abadi Malang. The research focuses on the challenges of account blockages on social media and how SEO can improve content visibility and sales. Method: A descriptive qualitative approach was used, with data collected through observations and interviews. The study analyzed current SEO strategies and identified issues related to social media account blockages, proposing solutions to overcome them. Practical Applications: The findings offer practical solutions for businesses using SEO to enhance visibility and drive sales. Strategies include diversifying content across multiple accounts and reducing identical posts to avoid account blockages, optimizing digital marketing efforts. Conclusion: The study demonstrates the importance of SEO in digital marketing, showing how it can improve content visibility and sales. Despite challenges like social media account blockages, effective SEO can significantly enhance marketing outcomes for businesses like CV Saudagar Kaya Abadi Malang.